HAPPINESS INDEX AMONG NURSING STUDENTS IN UNIVERSITI TEKNOLOGI MARA - Suzana Yusof; Fatimah Sham; Norhafizatul Akma Shohor; Aisyah Jamalluddin; Naz Azfahanee Rambli; Nur Syamimi Zulkifli (Journal of Islamic, Social, Economics and Development, 2021)
Happiness is a crucial factor in human life. Nursing students' life can be challenging due to many factors that may contribute to their happiness index. Objective: This study aims to identify the happiness index among full-time nursing students in UiTM Puncak Alam Campus. Method: A quantitative cross-sectional study was conducted using the set of happiness questionnaires among nursing students. Result: Findings from the population of 161 nursing students indicated that the majority of students rated their happiness index as happy with 70.2%. Students' age 20 years old and below were the happiest age group with 71.7%, females showed high happiness index with 72.3%, degree students were happier than diploma students with 70.3%, and lastly, students with CGPA range 3.49 and below was the happiest group with 71.1%. Conclusion: Conclusively that most of the nursing students in UiTM Puncak Alam Campus were happy although they have to deal with the heavy academic curriculum, many assignments, and clinical practices of every semester.